Theoretical insight into the mechanism of photoreduction of CO2 to CO by graphitic carbon nitride. Issue 3 (7th January 2019) - Wu, Hong-Zhang; Bandaru, Sateesh; Huang, Xiao-Li; Liu, Jin; Li, Li-Li; Wang, Zhenling
Abstract : The assistance of the proton plays a key role in the photoreduction of CO2 to CO. Abstract : Graphitic carbon nitride (g-C3 N4 ) is a promising photocatalyst for the reduction of CO2 into fuels. However, the reduction mechanism of CO2 using g-C3 N4 is not clear in the literature. In the present study, the fixation of CO2 and the formation of carbamate on the nitrogen atom at the edge of g-C3 N4 were investigated using first-principles density functional theory. The calculated results shows that two adjacent bare nitrogen atoms at the edge of g-C3 N4 could be the activation sites for the proton and CO2 molecule respectively, which are crucial to the formation of carbamate. The calculated energy barrier of carbamate formation is 0.95 eV for a preferential pathway. From studies on these micro processes, we propose a mechanism with proton assistance for the g-C3 N4 -catalyzed photoreduction of CO2 to CO.